The high homeostatic model assessment of insulin resistance as risk factor for acne vulgaris - I Gusti Ayu Agung Praharsini; Anak Agung Gde Putra Wiraguna; Stefani Nurhadi (Bali Dermatology and Venereology Journal, 2018)
Background: Acne vulgaris (AV) is a common chronic skin disease involving blockage and or inflammation of pilosebaceous glands which usually affects teenagers and young adults. Elevated sebaceous gland secretion, Propionibacterium acne colonization and inflammation, high androgen effects, and follicular hyperproliferation are the main pathogenic factors of AV. IGF-1 and insulin were studied to stimulate sebaceous lipogenesis. In the skin, besides inducing lipid production in human sebocytes IGF-1 also induces keratinocyte proliferation in vitro and in vivo. HOMA-IR is an examination to determine insulin activity in the basal state.Objective: To prove that high HOMA-IR value is a risk factor for the occurrence of acne vulgaris.Methods: This study is a case control analytic study by comparing HOMA-IR in subjects with AV (case group) and non AV (control group). AV is diagnosed based on clinical predilection. Insulin testing was carried out by the immulite 2000 device through the immunochemiluminescent method.Results: Mean HOMA-IR of case group is 2.63 Â± 0.29 meanwhile in the control group was 1.71 Â± 0.26 (p <0.001). Subjects with high HOMA-IR had 4.8 times higher risk to experience AV compared to patients with normal HOMA-IR values (p <0.001; 95% IK 2,765-8,332). Conclusion: HOMA-IR values in acne patients were higher than controls. A high HOMA-IR value is an AV risk factor.